THE USE OF THE INDWE SANDSTONE AS A STRATIGRAPHIC MARKER IN THE MOLTENO STAGE OF THE KARROO SYSTEM - Turner, B. R. (My University, 1969)
In recent years it has become increasingly apparent that some of the early concepts of stratigraphic relationships in the Molteno Stage of the Karroo system are not wholly acceptable. Apart from the monotonously repetitive lithology, the lack of fossil data makes regional correlation difficult. Early attempts at correlation were based largely on the supposedly distinctive lithology of certain sandstone beds. The Indwe Sandstone, in particular, has received special attention and its general acceptance by stratigraphers as a lithostratigraphic marker of regional significance is now firmly entrenched in the literature.